2008
DOI: 10.1017/s0031182008005271
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in host phenotype manipulation by an acanthocephalan: time to be transmitted?

Abstract: Many complex life cycle parasites exhibit seasonal transmission between hosts. Expression of parasite traits related to transmission, such as the manipulation of host phenotype, may peak in seasons when transmission is optimal. The acanthocephalan Acanthocephalus lucii is primarily transmitted to its fish definitive host in spring. We assessed whether the parasitic alteration of 2 traits (hiding behaviour and coloration) in the isopod intermediate host was more pronounced at this time of year. Refuge use by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…A seasonal effect of manipulation was also documented in gammarids infected by acanthocephalan parasites 71 , although the mechanisms explaining such seasonality were not identified. Our study supports the hypothesis made by Benesh et al 67 who suggested that seasonal changes in manipulation might not be caused by proximal abiotic conditions. In other studies, only light properties were shown to affect manipulation 68,69 , while other factors such as the quantity of resources available did not affect manipulation either 45 .…”
Section: Groupsupporting
confidence: 93%
“…A seasonal effect of manipulation was also documented in gammarids infected by acanthocephalan parasites 71 , although the mechanisms explaining such seasonality were not identified. Our study supports the hypothesis made by Benesh et al 67 who suggested that seasonal changes in manipulation might not be caused by proximal abiotic conditions. In other studies, only light properties were shown to affect manipulation 68,69 , while other factors such as the quantity of resources available did not affect manipulation either 45 .…”
Section: Groupsupporting
confidence: 93%
“…Several manipulative parasites also present seasonal variations, not only in their prevalence, but also in the intensity of their manipulation. For instance, some acanthocephalan parasites induce a stronger change in refuge use by their isopod hosts during spring, compared to summer or fall ( Benesh et al., 2009a ). Benesh et al.…”
Section: How Environmental Changes Can Alter the Roles Of Manipulativmentioning
confidence: 99%
“…For instance, some acanthocephalan parasites induce a stronger change in refuge use by their isopod hosts during spring, compared to summer or fall ( Benesh et al., 2009a ). Benesh et al. (2009a) suggested that seasonal variations in isopod behavioral alterations could result from a manipulation strategy adjusted to seasonal variation in the diet of definitive hosts.…”
Section: How Environmental Changes Can Alter the Roles Of Manipulativmentioning
confidence: 99%
“…Bakker et al, 1997;Maynard et al, 1998;Médoc et al, 2006;Kaldonski et al, 2008;Benesh et al, 2009), where the amphipods serve as intermediate hosts that have to be ingested by birds or fishes, the parasite's final hosts (Crompton & Nickol, 1985). Fish parasites of the genus Pomphorhynchus are known to manipulate the photophobic behaviour (Bethel & Holmes, 1973;Kennedy et al, 1978;Bakker et al, 1997), the response to predator fish cues (Baldauf et al, 2007;Perrot-Minnot et al, 2007) as well as the activity of their amphipod intermediate hosts, and make them more conspicuous as the yellow-orange cystacanths are clearly visible through their cuticle (Bakker et al, 1997).…”
Section: Introductionmentioning
confidence: 99%